Simulation and Configuration Mpls VPN Technology on Computer Networks Using GNS3 - Zahrul Maizi (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
Advances in technology, especially information will help the progress of a company that uses it. Where information can be obtained from anywhere quickly and without knowing the distance. Needs service link between cities/ regions certainly can not be separated as the development of technology where the limitations of the place is not a barrier to be connected. For that we need to create a new system by using a VPN type Site to Site and failover link . configure Site to Site VPN Client on Router device , it will add Router performance that is continuously running the VPN Client-Server function plus more with its main function for connection Internet and local area network (LAN) networks . It is not efficient considering the fast, precise and continuous data exchange. Multiprotocol Label Switching (MPLS) is a network architecture for combining labeling mechanisms in layer 2 with routing in layer 3 to speed up packet delivery. MPLS VPN is used to create a private path from one node to another, and simplify packet routing and optimizing route selection (path) to the destination. MPLS VPN with its labeling mechanism can overcome the above problems . Fa ilover link itself aims to provide availability on the network by performing a backup link if the main link has problems.Keywords: Information, simulation, configuration